2020
DOI: 10.22541/au.160193423.36406539/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Wasatch Environmental Observatory: A mountain to urban research network in the semi-arid Western US

Abstract: The Jordan River Basin, and its seven sub-catchments of the Central Wasatch Mountains immediately east of Salt Lake City, UT, are home to an array of research infrastructrure that collectively form the Wasatch Environmental Observatory (WEO). Each sub-catchment is comprised of a wildland to urban land use gradient that spans an elevation range of over 2000 m in a linear distance of˜25km. Geology varies across the sub-catchments, ranging from granitic, intrusive to mixed sedimentary rocks in uplands that drain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Interannual variability in subsurface water storage is quantified using mean daily streamflow in January when catchments are snow covered and isotopic and geochemical analyses indicate that streamflow from these and other regional watersheds is derived from groundwater (Follstad Shah et al, 2019;Gabor et al, 2017;Hall et al, 2016;Follstad Shah et al, 2021). The annual cycle of streamflow in these catchments is typical for montane snowmelt systems with peak discharge in spring and early summer during melt, annual minimum in late summer when ET is high, and a slow rebound in fall as plants senesce followed by stabilization in mid-winter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interannual variability in subsurface water storage is quantified using mean daily streamflow in January when catchments are snow covered and isotopic and geochemical analyses indicate that streamflow from these and other regional watersheds is derived from groundwater (Follstad Shah et al, 2019;Gabor et al, 2017;Hall et al, 2016;Follstad Shah et al, 2021). The annual cycle of streamflow in these catchments is typical for montane snowmelt systems with peak discharge in spring and early summer during melt, annual minimum in late summer when ET is high, and a slow rebound in fall as plants senesce followed by stabilization in mid-winter.…”
Section: Methodsmentioning
confidence: 99%
“…Trend analysis using PRISM data, especially when it includes SNOTEL stations, is subject to artifacts associated with changes in number, type, and location of instruments. Fortunately, northeast Utah has a large number of long-term climate observations (Horel et al, 2002;Follstad Shah et al, 2021) and a hydroclimatic reanalysis has indicated minimal bias in the region (Maurer et al, 2002). Additionally, changepoint analysis was used to identify when any periods of increase or decrease began and no changes were associated with the instrument changes at local SNOTEL sites.…”
Section: Tablementioning
confidence: 99%